New progress in pediatric allergic rhinitis - Cheng, Miao; Dai, Qianqian; Liu, Zhi; Wang, Yulin; Zhou, Cuiyun (Frontiers in Immunology, 2024)
The prevalence of allergic rhinitis (AR) in children is steadily increasing, and its onset is closely associated with genetic factors, living environment, and exposure to allergens. In recent years, an increasing number of diagnostic methods have been employed to assist in diagnosing AR. In addition to pharmaceutical treatments, personalized approaches such as environmental control and allergen-specific immunotherapy are gradually gaining popularity. In this article, we reviewed recent research on the etiology, diagnostic classification, treatment methods, and health management of AR in children. These insights will benefit the implementation of personalized diagnosis and treatment for children with AR, promoting health management strategies that improve symptoms and quality of life.